FACTORS AFFECTING THE MOTIVATION ON INTEREST STUDENTS TO PARTICIPATE AN ACCOUNTING PROFESSION EDUCATION (Empirical Study on Accounting Students in Four State University Est Java) - Puspita Nurindah Dewi; Zaki Baridwan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This research aimed to determine the factors that affect the interests of accounting students at four State University in East Java to follow PPAk. The variables used are quality motivation, career motivation, economic motivation, achievement motivation, and awards / recognition motivation. The population in this research is a student majoring in Accounting S1 2011 wich is still active in four State University in East Java. Samples used in this research is 363 respondents. In the research data used primary data obtained from questionnaire. The method used in this study is a survey method. Data were tested by using SmartPLS ver. 2.0 M3. The results of this research shows that the career motivation, achievement motivation, and awards/recognition motivation have a significant influence toward the interest of accounting students to follow an PPAk. While quality motivation and economic motivation has no significant influence toward interest of accounting students to follow an PPAk. Keywords : Quality Motivation, Career Motivation, Economic Motivation, Achievement Motivation, Awards/Recognition Motivation, Interest, Accounting Profession Education